2003
DOI: 10.1007/s10120-003-0238-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of reconstruction methods after gastrectomy using a new type of examination: digestion and absorption test with stable isotope 13 C-labeled lipid compound

Abstract: absorption of medium-chain triglycerides, and the patients also showed a better physiological state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…Hyperglycemia following intake of 75-g glucose frequently occurs in patients undergoing pancreatoduodenectomy, because pancreatoduodenectomy includes reconstruction of the alimentary tract or gastrectomy, and these procedures allow carbohydrate influx directly into the small intestine. Several investigators reported that patients with subtotal gastrectomy frequently developed hyperglycemia after an oral glucose tolerance test [27,28]. In contrast, serum HbA 1c levels are usually used as an indicator of glycemic control and do not require glucose ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia following intake of 75-g glucose frequently occurs in patients undergoing pancreatoduodenectomy, because pancreatoduodenectomy includes reconstruction of the alimentary tract or gastrectomy, and these procedures allow carbohydrate influx directly into the small intestine. Several investigators reported that patients with subtotal gastrectomy frequently developed hyperglycemia after an oral glucose tolerance test [27,28]. In contrast, serum HbA 1c levels are usually used as an indicator of glycemic control and do not require glucose ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that moderate malnutrition is often associated with gastric cancer surgery [16] , and that esophagogastrostomy reconstruction is more favorable to the natural food passage of the duodenum than esophagojejunostomy. It has been shown that independent prognostic factors such as ensuring radical cure, maintaining food passage in the duodenum, and less excision of the stomach, are very important for postoperative QOL [17,18] . A high incidence of reflux symptoms after simple esophagogastrostomy has prompted the development of several novel reconstructions to prevent reflux [12,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we performed the 13 C-labeled mixed triglyceride breath test to assess digestive and absorptive ability after subtotal gastrectomy. 13 C is a stable isotope, and is reported to represent 1.1% of existing carbon atoms in nature [14]. As it is not radioactive, and dose not have any possibility of explosion or contamination, it can be safely used for children and pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduced postprandial motor response suggests a hormonal mediator abnormality [23]. Comparison of these reconstructive routes is considered a feasible method for assessment of nutrition in patients who underwent different gastric reconstructive procedures following gastrectomy [14]. …”
Section: Discussionmentioning
confidence: 99%